Impact of Marijuana Use on Lung Health - Bando, Joanne M.; Tashkin, Donald P.; Barjaktarevic, Igor Z. (Seminars in Respiratory and Critical Care Medicine, 2024)
The widespread use of marijuana in the context of increasing legalization has both short- and long-term health implications. Although various modes of marijuana use—smoked, vaped, or ingested—may lead to a wide scope of potential systemic effects, we focus here on inhalational use of marijuana as the most common mode with the lung as the organ that is most directly exposed to its effects. Smoked marijuana has been associated with symptoms of chronic bronchitis and histopathologic changes in airway epithelium, but without consistent evidence of long-term decline in pulmonary function. Its role in immunomodulation, both for risk of infection and protection against a hyperinflammatory host response to infection, has been suggested in animal models and in vitro without conclusive extrapolation to humans. Marijuana smoke contains carcinogens like those found in tobacco, raising concern about its role in lung cancer, but evidence is mixed and made challenging by concurrent tobacco use. Vaping may offer a potential degree of harm reduction when compared with smoking marijuana with reduction of exposure to several toxins, including carbon monoxide, and reduction in chronic respiratory symptoms. However, these potential benefits are counterbalanced by risks including vaping-associated lung injury, potentially more intense drug exposure, and other yet not well-understood toxicities. As more states legalize marijuana and the federal government considers changing this from a Schedule I to a Schedule III controlled substance, we anticipate an increase in prospective medical studies concerning the risks related to marijuana use. This review is based on currently available data concerning the impact of inhaled marijuana on lung health.
Keywords: marijuana; cannabis; lung health